The myth of Aunt Jemima : - Diane Roberts. (Routledge, 1994)
1. Uncle Tom's Cabin: An authentic ghost story -- 2. "Instigated by the Devil": The South and Harriet Beecher Stowe -- 3. Miss Wright, Mrs Trollope and Miss Martineau: or, Three British women look at American slavery -- 4. The Strange Career of Fanny Kemble -- 5. Olla Podrida America: Lydia Maria Child and radical miscegenation -- 6. Jemima and Jezebel in the New South: Twentieth-century women on race -- Epilogue: Making the word the thing.